2016
DOI: 10.1007/s11605-016-3243-7
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Lymph Node Status and Extent of Lymphadenectomy in Pancreatic Neuroendocrine Tumors Confined To and Extending Beyond the Pancreas

Abstract: While in T1-T2 pNET N1 status is a predictor of negative OS, similar outcome between NX and N0 supports limited LN resection in selected patients. Extended LA is unlikely to be helpful in T3-T4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(26 citation statements)
references
References 23 publications
4
21
0
1
Order By: Relevance
“…Surprisingly, we found the extent of ELNs failed to demonstrate any survival benefit in entire cohort (ELNs > 12 vs. ELNs ≤ 12) or in the negative lymph node metastasis pNENs (ELNs > 28 vs. ELNs ≤ 28). Similar to our findings, Conrad et al [ 28 ] also demonstrated that the extent of ELNs (ELNs ≥ 10) failed to show significant survival advantage.…”
Section: Discussionsupporting
confidence: 92%
“…Surprisingly, we found the extent of ELNs failed to demonstrate any survival benefit in entire cohort (ELNs > 12 vs. ELNs ≤ 12) or in the negative lymph node metastasis pNENs (ELNs > 28 vs. ELNs ≤ 28). Similar to our findings, Conrad et al [ 28 ] also demonstrated that the extent of ELNs (ELNs ≥ 10) failed to show significant survival advantage.…”
Section: Discussionsupporting
confidence: 92%
“…In the current study, we showed that 26.7% (27/101) NF-PNETs patients had LN metastases when diagnosed. Furthermore, LN metastases was associated with decreased DFS, which was similar to previous studies 9 , 10 . Interestingly, our study also showed that preoperative NLR ≥ 1.80, tumor size ≥ 2.5 cm and symptomatic diagnosis were independently associated with LN metastases for patients undergoing resection of NF-PNETs.…”
Section: Discussionsupporting
confidence: 90%
“…The current American Joint Committee on Cancer Staging (AJCC) and European Neuroendocrine Tumor Society (ENETS) considers tumor size, lymph node (LN) metastasis, and presence of distant metastasis in its staging criteria 6 8 . In addition, more and more evidence demonstrated that LN metastasis was an independent prognostic factor for PNETs 9 , 10 . Therefore, the investigation of factors related to LN metastases has a great clinical significance.…”
Section: Introductionmentioning
confidence: 99%
“…Lymph node involvement is one of the most powerful prognostic factors after surgical resection for PanNETs [53][54][55][56][57][58] . The optimal number of lymph nodes to be resected during pancreatic resection due to PanNETs is unknown [57] .…”
Section: Which Is the Role Of Lymphadenectomy During Pancreatic Resecmentioning
confidence: 99%